Abordagem inicial de lesões mamárias por biopsia helicóide: estudo experimental - Souza, Eliel de (2010)
OBJECTIVE: Evaluating the kit-Bh performance in carrying out of breast biopsies. METHODS: They were randomly selected a sample of 30 patients with breast cancer undergoing mastectomy, based on the results of a pilot study from February 2008 to April 2010. They were excluded women with had not palpable, stone-hard consistency tumors, previous surgical manipulation or that contains liquid. Using the helicoid biopsy Kit (kit Bh) and an equipment Core biopsy with cannula and needle and 14 gauge respectively, it was collected a fragment of sound equipment in the area and in tumors in each specimen, totaling 120 fragments for histological study. For data analysis, it was defined a 95% confidence level and used the SPSS-13 version, the Kappa index and the parametric Student t test. RESULTS: Mean age of patients was 51.6 years (± 11.1 years). The infiltrating ductal carcinoma showed a higher incidence, 26 cases (86.7%). The Core biopsy had a sensitivity of 93.3%, specificity of 100% and accuracy 96.7%, while the helicoid biopsy had a sensitivity of 96.7%, specificity of 100% and accuracy 98.3%. By comparing the histology of tumors and the fragments of biopsies, there was high degree of agreement in diagnoses (kappa of 0.93 with p <0.05) CONCLUSION: Both devices provided the histological diagnosis of lesions with high accuracy. Results of this study showed that the helicoid biopsy is a reliable alternative in 22 the preoperative diagnosis of breast lesions. Further studies in vivo better will define the role of Kit Bh in the diagnosis of these lesions